Implementing skills development programme in the public service : a case of the office premier: Mpumalanga Provincial government - Mathe, Lindiwe Jeanneth (My University, 2019)
The purpose of the study was to investigate the implementation of skills development programmes in the public service. The study was conducted in the Office of the Premier. The aim of the study was to determine the effectiveness of the implementation of skills development programmes in the Office of the Premier in the Mpumalanga Provincial Government. This was done to gain a deeper understanding of the challenges that unit managers face during the implementation of skills development programmes in the area of study. The relevant data was obtained through empirical investigation and interviews. This data was obtained from the seventy (70) respondents who participated in the study. To achieve this process, the researcher obtained quantitative data from fifty (50) officials and qualitative data from twenty (20) managers. The study revealed that there were challenges that hamper the implementation of skills development in the Office of the Premier. Problems related to Acts of Parliament, inadequate feedback, lack of impact assessment, clarity on policy guidelines and a lack alternative strategies were regarded as the main challenges faced by the stakeholders on the implementation of skills development in the area of the study. However, there were also benefits that were derived from Human Resource Development indicated by the respondent related to enhancement of good performance and career advancement in the Office of the Premier. The study has suggested and recommended the empowerment of officials on issues related to legislation and clarity of policies. The study also recommended that the senior managers should also conduct impact assessments and develop alternative strategies that may enhance skills development in the area of the study. The implementation of the recommendations and the findings may assist the stakeholders to enhance the implementation of skills development in the Office of the Premier
Thesis(MPA.) -- University of Limpopo, 2019
Keywords: Skill development; Public service; Development programme; Development programme; Development; Public administration; Ability